Inward foreign direct investment and domestic entrepreneurial activity - Valentini, Giulia (2017)
This dissertation investigates the relationship between inflows of foreign direct investment and the rate of domestic entrepreneurial activity, paying attention to the possible difference in this relationship between developed and developing nations. The rationale for this analysis lies in the fact that both FDI and entrepreneurial activity are important drivers of economic development and, consequently, a critical issue for international business. In order to examine this matter, a panel data analysis of data from ten developed and developing countries over seven years was executed, including several control variables for economic development and entrepreneurship. The results show that FDI appears to be a statistically significant predictor of entrepreneurial activity, affecting it positively and, therefore, supporting positive spill over theories of FDI in relation to entrepreneurship. However, differences in effect of FDI on entrepreneurship between developing and developed economies could not be observed.